MEDICINAL PLANT USE BY SUNDANESE ETHNIC IN NYANGKEWOK HAMLET, SUKABUMI REGENCY - Ken Dara Cita; Ratna Sari Hasibuan; Prapto Waluyo; Tun Susdiyanti (Department of Forest Resources Conservation and Ecotourism - IPB University, 2020)
Sundanese ethnic in Nyangkewok hamlet, Sukabumi has been using medicinal plants to cure and prevent illness. This research aims to identify and describe medicinal plant use by Sundanese Ethnic with indigenous knowledge in Nyangkewok Hamlet, Sukabumi. This research was conducted from February to May 2020 with qualitative method. The research resulted in 103 species of 42 plant families used by the Sundanese community in Nyangkewok Hamlet with Zingiberaceae dominant family, the most used part of the medicinal plants was leaves. Key word: indigenous knowledge, medicinal plants, Sundanese ethnic